Tooth Side Centering Modeling and Load Analysis of Involute Splines - Qin Yuanning; Dong Hongtao; Lei Duncai; Chen Siyu (Jixie chuandong)
Splines have many advantages such as high transmission torque, self-centering and so on, and have a wide range of applications in the transmission system. Ideally, splines are evenly loaded on each tooth. However, manufacturing and installation errors can cause differences in tooth clearances, and load is no longer evenly distributed between spline teeth, which reduces the spline life. In the environment of vibration, the relative radial movement between internal splines and external splines causes the relative clearance of each tooth to change continuously, and the load distribution between spline teeth is more complicated. In order to further understand the load distribution rule between spline teeth, the dynamic model of centering spline pair on the tooth side is established, and Newmark-β method is used to solve the system dynamic equation. The calculation results show that the engagement forces of spline teeth are very sensitive to tooth side clearance and are prone to the offset load. In addition, the influence of the contact length and the precision class on the load distribution between spline teeth is discussed. It is found that the longer the contact length and the lower the precision class, the worse the spline bias load will be. Finally, the contact analysis of the tooth-side mating spline pair is carried out and the meshing forces of each spline tooth calculated by two methods are compared, which verifies the correctness of the model in this study.